PENGARUH KECERDASAN EMOSIONAL (EQ), KECERDASAN INTELEKTUAL (IQ), KECERDASAN SPIRITUAL (SQ), KECERDASAN SOSIAL, ETIKA PROFESI, KOMPETENSI DAN INDEPENDENSI TERHADAP KINERJA AUDITOR (Studi Pada Kantor Akuntan Publik Pekanbaru, Padang, Medan) - Ade Chandra Widana; Yunieta Yunieta; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research to examined the influence of emotional intelligence, intellectual intelligence, spiritual intelligence social intelligence, professional ethic, competence and independence the performance of the auditor. The population in this study all auditors who worked in public accounting firm in Pekanbaru, Padang, and Medan. This research used 63 sample of quetionnaires response from staff of public accountant firm in Pekanbaru, Padang, Medan. Analysis model used in this study is the multiple linear regression analysis with SPSS Version 20.00. The result of this study is showed that emotional intelligence, intellectual intelligence, spiritual intelligence social intelligence, professional ethic, competence and independence have significant influence the performance of the auditor. Simultaneous regression test (F-test) showed that all dependent variable have significant influence to the dependent variable. The coefficient determination (R2 ) effect by all independent variable are 91% while the remaining 9% influence by other variables were not examined in this study.Keyword : Emotional Intelligence, Intellectual Intelligence, Spiritual Intelligence Social Intelligence, performance of the auditor